A flexible transparent heater with ultrahigh thermal efficiency and fast thermal response speed based on a simple solution-processed indium tin oxide nanoparticles-silver nanowires composite structure on photo-polymeric film. (22nd March 2018) - Kim, Chaewon; Lee, Mi Jung; Hong, Sung-Jei; Kim, Young-Sung; Lee, Jae-Yong
Abstract: In this study, a composite structure consisting of indium tin oxide nanoparticles (ITO-NPs)-silver nanowires (Ag NWs) on photo-polymeric film was intensively studied for flexible transparent heater with ultrahigh thermal efficiency and fast thermal response speed. For cost-effective manufacturing, a simple solution process was employed to make low-cost composite structure by using 0.15 wt% Ag NWs and 5 wt% ITO-NPs solution. Among 3 types, namely, 2-layer (Ag NWs/ITO-NPs), 2′-layer (ITO-NPs/Ag NWs), and 3-layer (ITO-NPs/Ag NWs/ITO-NPs) sample, the composite structure was optimized as 3-layer, which raised temperature by more than 15% compared to the 1-layer sample (Ag NWs only) at the same voltage. In addition, the 3-layer sample made on Norland optical adhesive 63 (NOA 63) photo-polymeric film exhibited good characteristics as a flexible transparent heater. Optical transmittance at 550 nm (T550 ) of the 3-layer sample was 89.92%, which was similar to that of the 1-layer sample (90.87%). However, sheet resistance (Rs ) of the 3-layer sample was 19.56 Ω/sq., which was remarkably lower than that of the 1-layer sample, 78.45 Ω/sq. In addition, an ultrahigh thermal efficiency (328 °C/(W/cm 2 )) was achieved from the 3-layer composite structure on the NOA 63 film. Thermal response speed of the 3-layer sample was as ultrafast as 10 s and temperature within 90 °C and 100 °C stably increased and decreased during 60 cycles when applying 5 V. Moreover, the 3-layer sample stably generated heat even under the extreme bending diameter of 5 mm, and heat-generating properties, such as thermal response speed, saturated temperature, and cooling rate, remained almost unchanged even after bending for 1000 cycles.